Réponse :
C₆H₁₂ + O₂ → CO₂ + H₂O
On a :
Réactifs :
Atomes de carbone = 6
Atomes d'hydrogène = 12
Atomes d'oxygène = 2
Produits :
Atomes de carbone = 1
Atomes d'hydrogène = 2
Atomes d'oxygène = 2 + 1 = 3
On rééquibre l'équation :
C₆H₁₂ + 9O₂ → 6CO₂ + 6H₂O
Maintenant, on a :
Réactifs :
Atomes de carbone = 6
Atomes d'hydrogène = 12
Atomes d'oxygène = 9 × 2 = 18
Produits :
Atomes de carbone = 6
Atomes d'hydrogène = 6 × 2 = 12
Atomes d'oxygène = 6 × 2 + 6 × 1 = 12 + 6 = 18
Donc l'équation est bien équilibrée.
C₆H₁₂ + 9O₂ → 6CO₂ + 6H₂O